2010
DOI: 10.1017/s0047279410000644
|View full text |Cite
|
Sign up to set email alerts
|

Homelessness and the Mobile Shelter System: Public Transportation as Shelter

Abstract: Those without housing often use public space differently than those who are housed. This can cause dilemmas for and conflicts among public officials as guardians of public space and goods. In this paper, we look at one such utilisation of space from the perspective of those who board 24-hour public transportation routes and ride the bus all night for shelter. We describe the results of a preliminary survey, observations and informal conversations with unhoused riders on the bus over three nights in one county … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 14 publications
0
12
0
Order By: Relevance
“…Also, because of multiple claims made about needing a clearer understanding of the gendered context of homelessness, research has sought to explore the specific risk factors to homelessness that are unique to males and those unique to females (Zugazaga, 2008), or particular behaviours of homeless men and those of homeless women (Nichols and Ca'Zares, 2006). That research has led to useful suggestions for social policy and social programming.…”
Section: Nature Of the Relationship And The Impact On Housingmentioning
confidence: 99%
“…Also, because of multiple claims made about needing a clearer understanding of the gendered context of homelessness, research has sought to explore the specific risk factors to homelessness that are unique to males and those unique to females (Zugazaga, 2008), or particular behaviours of homeless men and those of homeless women (Nichols and Ca'Zares, 2006). That research has led to useful suggestions for social policy and social programming.…”
Section: Nature Of the Relationship And The Impact On Housingmentioning
confidence: 99%
“…In a study of 974 women who were homeless in Los Angeles County, one-third reported being kicked, bitten, hit with a fist or an object, choked, beaten, burned, or threatened or harmed with a gun in the past 12 months (Wenzel, Leake, & Gelberg, 2001). Women who are unhoused adopt a range of strategies to try to keep safe including riding public transportation overnight (Nichols & Cazares, 2011), isolating themselves from others, seeking male protectors or companions, wearing baggy clothes to downplay their bodies, and trying to appear tough (Huey & Berndt, 2008;Stevenson & Neale, 2012). Although the farm offered at least some protection to those who slept or stored their belongings nearby, great risk remained.…”
Section: Interpersonal Relationships and Supportmentioning
confidence: 99%
“…The study was initiated as part of an undergraduate class I was teaching on Applied Sociology. Eleven students and I undertook the data collection, spending three nights riding the bus and talking to and collecting standardized data from riders who identified as homeless (Nichols 2011). In talking to riders, I came to recognize the use of the bus for shelter as an example of a social desire path at work (Nichols 2014).…”
Section: Characteristics Of Social Desire Pathsmentioning
confidence: 99%
“…Transportation officials were frustrated that persons choose to ride the bus rather than go to emergency shelters and asked homeless service providers to fix "the problem". The study involved spending nights on the bus talking to and collecting survey data from riders who identified as homeless (Nichols and Cázares 2011;Nichols, Cázares, and Rodriguez 2012).…”
mentioning
confidence: 99%